The Implementation of Character Education in Kalimantan, Indonesia: Multi Site Studies - Abdi, Muhammad Iwan (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
This research was inspired by some of the realities that the author found related to the implementation of character education, especially in several regencies/cities in East Kalimantan. Apart from the author’s concern toward the case of the moral decadence of the nation's children, this should be a demand and obligation for every educator to form the character of his students. Therefore, various models and innovations began to be developed by educational units led by creative teachers starting to package character-based learning designs and innovations. This research focuses on character models developed by the school. This research is a field work research that focuses on multi-site studies. Sources of data in this study include: teachers and students in several schools are the focus of research. The research locus is spread in several regions, namely: Tarakan, Bulungan, East Kutai and Bontang. The data collection techniques that the author uses in this study include: observations, interviews and documentations. Furthermore, the findings of the research data were processed using Milles and Hubberman's interactive analysis using the data reduction flow , data display and data conclusions . Based on the findings of the research, it can be concluded that the character values developed include: religious values, creative, independent and responsible, the spirit of nationality and love for the motherland, tolerance, communication and love the environment.